2014
DOI: 10.2217/bmm.13.131
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Plasma Leptin, Homocysteine and Nitric Oxide Levels With the Presence and Unstability of Coronary Artery Disease

Abstract: Some athrogenic effects of leptin may be mediated by affecting tHcy and NO levels. Plasma leptin, tHcy and NO levels showed significant contribution to CAD prediction and discrimination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 44 publications
0
14
0
2
Order By: Relevance
“…Most adipokines not only play a significant role in metabolic diseases [ 5 ], but also exert multiple effects on the function of vessels and heart [ 6 ]. Adipokines can accelerate atherosclerosis [ 7–9 ] and contribute to the incidence of acute coronary syndrome [ 10 , 11 ]. In recent years, novel adipokines are emerging and their roles in cardiovascular diseases are being investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Most adipokines not only play a significant role in metabolic diseases [ 5 ], but also exert multiple effects on the function of vessels and heart [ 6 ]. Adipokines can accelerate atherosclerosis [ 7–9 ] and contribute to the incidence of acute coronary syndrome [ 10 , 11 ]. In recent years, novel adipokines are emerging and their roles in cardiovascular diseases are being investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Basati et al 21 reported that low leptin levels are correlated with higher cardiovascular events and mortality in patients with stable coronary artery disease. Furthermore, some cardio protective effects of leptin have been reported in experimental settings.…”
Section: Introductionmentioning
confidence: 99%
“…Korelacija je bila značajno negativna prema trigliceridima, indeksu telesne mase BMI, jutarnjoj hiperglikemiji, po kriterijumima American Diabetes Association Criteria. [16,17].…”
Section: Diskusijaunclassified